2021
DOI: 10.5194/tc-2021-266
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High-resolution subglacial topography around Dome Fuji, Antarctica, based on ground-based radar surveys conducted over 30 years

Abstract: Abstract. The retrieval of continuous ice core records of more than 1 Myr is an important challenge in palaeo-climatology. For identifying suitable sites for drilling such ice, the knowledge of the subglacial topography and englacial layering is crucial. For this purpose, extensive ground-based ice radar surveys were done over Dome Fuji in the East Antarctic plateau during the 2017–2018 and 2018–2019 austral summers by the Japanese Antarctic Research Expedition, on the basis of ground-based radar surveys condu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Theoretical works including molecular dynamics simulations for different gases and ice conditions may shed light on the different relationships between δO 2 /N 2 and δAr/N 2 in different zones. Finally, the International Partnership for Ice Core Sciences regards the retrieval of an ice core containing ice older than 1 million years as highest priority (Fisher et al, 2013;Tsutaki et al, 2021). Our constraints on the permeation coefficients of the gases in ice might be useful for predicting the magnitude of diffusive smoothing of air composition in such an ice core.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretical works including molecular dynamics simulations for different gases and ice conditions may shed light on the different relationships between δO 2 /N 2 and δAr/N 2 in different zones. Finally, the International Partnership for Ice Core Sciences regards the retrieval of an ice core containing ice older than 1 million years as highest priority (Fisher et al, 2013;Tsutaki et al, 2021). Our constraints on the permeation coefficients of the gases in ice might be useful for predicting the magnitude of diffusive smoothing of air composition in such an ice core.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1(b) demonstrates that the ice coring site was very close (within 10 km) to the present dome summit. At the present time with the Holocene climate, DF is associated with a steep north-south surface mass balance gradient (Fujita et al, 2011;Tsutaki et al, 2021). We suggest that this morphology demonstrates that the DF summit has migrated along this gradient in the north-south direction during glacial and interglacial periods over which the accumulation rate changed dramatically (e.g., Parrenin et al, 2016).…”
Section: Sample Preparationmentioning
confidence: 74%
“…Although the precise thicknesses of thin sections are not provided in Wang et al (2003) or Durand et al (2007Durand et al ( , 2009 (missing data are indicated by the # symbol in this table), it can be assumed that the thicknesses of sections prepared for optically based COF measurements were approximately 0.5 mm or less. , 2011;Tsutaki et al, 2022). We suggest that this morphology demonstrates that the DF summit has migrated along this gradient in the north-south direction during glacial and interglacial periods over which the accumulation rate changed dramatically (e.g., Parrenin et al, 2016).…”
Section: Sample Preparationmentioning
confidence: 78%